# Factoring With Special Forms

Factoring with special forms is a process of using identities to help with different factoring problems.

#### Contents

## Factoring by Difference of Squares

Factoring binomials of the form $x^2 - y^2= (x-y)(x+y):$

This approach applies the difference of two squares identity.

Factor $x^2 - 16$.

We have

$x^2 - 16 = x^2 - 4^2 = (x-4)(x+4).\ _\square$

Factor $x^4 - 25y^4$.

We have

$x^4 - 25y^4 = \big(x^2\big)^2 - \big(5y^2\big)^2 = \big(x^2 - 5y^2\big)\big(x^2 + 5y^2\big).\ _\square$

Factor $9x^3y - 36xy$.

We have

$9x^3y - 36xy = 9xy\big(x^2 - 4\big) = 9xy\big(x^2 - 2^2\big) = 9xy(x-2)(x+2).\ _\square$

Factor $(x+1)^2 - 9(x-2)^2$.

We have

$\begin{aligned} (x+1)^2 - 9(x-2)^2 &= (x+1)^2 - \big(3(x-2)\big)^2 \\ &= \big((x+1) - 3(x-2)\big) \big((x+1) + 3(x-2)\big) \\ &= (x + 1 -3x + 6)(x + 1 + 3x - 6) \\ &= (-2x + 7)(4x - 5). \ _\square \end{aligned}$

## Factoring by Sum and Difference of Cubes

Factoring binomials of the form $x^3 + y^3 = (x+y)\big(x^2 - xy + y^2\big)$ and $x^3 - y^3 = (x-y)\big(x^2 + xy+ y^2\big):$

This approach applies the sum and difference of cubes identity.

Factor $27x^3 - y^3$.

We have

$\begin{aligned} 27x^3 - y^3 &= (3x)^3 - y^3 \\ &= (3x - y)\big((3x)^2 + 3xy + y^2\big) \\ &= (3x-y)(9x^2 + 3xy + y^2). \ _\square \end{aligned}$

Factor $64x^3 + 27y^3$.

We have

$\begin{aligned} 64x^3 + 27y^3 &= (4x)^3 + (3y)^3 \\ &= (4x + 3y)\big((4x)^2 - 12xy + (3y)^2\big) \\ &= (4x + 3y)\big(16x^2 -12 xy + 9y^2\big). \ _\square \end{aligned}$

## Factoring Perfect Square Trinomials

Factoring trinomials of the form $x^2 + 2xy + y^2 = (x+y)^2$ and $x^2 - 2xy + y^2 = (x-y)^2:$

Factor $x^2 + 6x + 9$.

We have

$x^2 + 6x + 3 = x^2 + 2(x \cdot 3) + 3^2 = (x+3)^2. \ _\square$

Factor $x^2 - 4x + 4$.

We have

$x^2 - 4x + 4 = x^2 - 2(x \cdot 2) + 2^2 = (x-2)^2. \ _\square$

Factor $25x^2 - 20x + 4$.

We have

$25x^2 - 20x + 4 = (5x)^2 - 2(5x \cdot 2) + 2^2 = (5x-2)^2. \ _\square$

Factor $16x^2 - 24xy + 9y^2$.

We have

$16x^2 - 24xy + 9y^2 = (4x)^2 - 2(4x \cdot 3y) + (3y)^2 = (4x-3y)^2. \ _\square$

**Cite as:**Factoring With Special Forms.

*Brilliant.org*. Retrieved from https://brilliant.org/wiki/factoring-with-special-forms/